The Experimental Investigation of Longmaxi Shale Dynamic Parameters under Water-Based Mud Soaking. (23rd June 2019) - Dong, Guangjian; Chen, Ping; Yuan, Heyi; Lu, Yudi
Abstract : Shale damage investigation is important in shale gas development. This paper is concerned with the experimental identification of ultrasonic wave velocities and damage mechanic parameters of Longmaxi shale under water-based mud soaking and confining pressure loading. The wave velocities increased with increasing confining pressure, while wave velocities decreased with increasing soaking time. The anisotropy of Young's modulus decreases when confining pressure increases. As soaking time increases, the anisotropy coefficient increases. As soaking time and confining pressure rise, the damage parameters also show complex changes. The results are beneficial for shale gas development.